Comparative Studies on the Functional Properties of Neem, Jatropha, Castor, and Moringa Seeds Oil as Potential Feed Stocks for Biodiesel Production in Nigeria (Global Journal of Science Frontier Research, 2012)
Fossil fuel resources are decreasing daily while biodiesel fuels are attracting increasing attention worldwide as blending components or direct replacements for diesel fuel in vehicle engines. This study investigated the physicochemical properties of oils extracted from Jatropha, neem, moringa and castor seeds for their suitability in biodiesel production. This is with a view to compare which of the oils has better functional properties for a quality biodiesel production. Our results has shown that all the oil from the plants seed study, have good physiochemical properties and are very good precursor for biodiesel synthesis.
Keywords: biodiesel; feedstock; biofuel; renewable